BUCKLING OF ANISOTROPIC PLATES BY THE RITZ METHOD - Yshii, Lucas Nobumichi; Santana, Rafael Christovão; Monteiro, Francisco Alex Correia; Lucena Neto, Eliseu (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
The Ritz method is used in the buckling analysis of anisotropic plates under several combinations of in-plane loads and boundary conditions. Ritz bases are generated from modified Legendre polynomials, and the plate rigidities are carefully chosen to provide thermodynamically admissible materials. The accuracy of the proposed approach is assessed by means of several examples solved by Â…nite element models.